Optimizing Big Data Capabilities and Management in Manufacturing Firms. A Sociotechnical Perspective - Zhao, Xiaoli (Transformations In Business & Economics, 2024)
The rapid growth in digital transformations in businesses has increased the volume of data available to firms for analysis. This change has led to a rise in the uptake of big data analytics (BDA) in different business dimensions to enhance organizational performance, creating significant opportunities for integration within manufacturing systems. By using a sociotechnical perspective, we explore the interplay between social and technical aspects of BDA using a qualitative systematic review of 86 studies. The findings indicate that manufacturing firms have to optimize both social and technical factors in BDA systems to enhance their performance. While advanced analytical capabilities of BDA like prescriptive analytics improve operational performance, manufacturing firms should also invest in enhancing their human resource capabilities, organizational culture, and information governance to align them with the requirements of BDA. In that regard, this study provides scholars and practitioners with an understanding of how to optimize big data capabilities within manufacturing firms and a basis for further research on BDA adoption.